The influence of technostress, work–family conflict, and perceived organisational support on workplace flourishing amidst COVID-19 - Harunavamwe, Martha; Ward, Chené (Frontiers in Psychology, 2022)
The remote working environment is characterised by excessive use of new technology and work activities that extend to personal time. It is expected of each employee to balance multiple roles whilst maintaining maximum performance and individual wellbeing; however, without adequate support from an organisation, employees languish instead of flourish. The current study applied a model to investigate the combined effect of technostress, work–family conflict, and perceived organisational support on workplace flourishing for higher education employees. The study followed a cross-sectional quantitative research framework. Data were collected from a sample of 227 academic and support staff employees from a selected residential University in South Africa. The results indicated that technostress through perceived organisational support and through work–family conflict influences workplace flourishing. No direct significant effect was reported between technostress and workplace flourishing. Technostress, work–family conflict, and perceived organisational support combined explained 47% variance in workplace flourishing. Perceived organisational support displayed the strongest direct effect on workplace flourishing, and technostress is a strong determinant of work–family conflict, which then mediates the relationship between technostress and workplace flourishing. The study concluded that providing organisational support and creating policies favourable to work–life balance assist employees in managing techno-overload, techno-invasion, and techno-complexity (technostress) better and enhance workplace flourishing. Although employees struggle in the remote working context with demands imposed by techno-overload, techno-invasion, and techno-complexity, the results indicate that perceived organisational support and balanced work life act as job resources that enhance emotional, psychological, and subjective wellbeing (workplace flourishing).